2011
DOI: 10.1038/ejcn.2011.15
|View full text |Cite
|
Sign up to set email alerts
|

Use of a common food frequency questionnaire (FFQ) to assess dietary patterns and their relation to allergy and asthma in Europe: pilot study of the GA2LEN FFQ

Abstract: Background/Objectives: Comparable international data on food and nutrient intake is often hindered by the lack of a common instrument to assess food intake. The objective of this study was within the Global Allergy and Asthma European Network of Excellence (GA 2 LEN), we developed and piloted a food frequency questionnaire (FFQ) to assess its validity in Europe. Subjects/Methods: Five countries participating in GA 2 LEN took part in the pilot study. A total of 200 adults aged 31-75 years were invited to comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 30 publications
1
59
0
Order By: Relevance
“…These studies provide plausibility that differences between ethnic groups in maternal or childhood diets might be able to explain some of the differences in early adult lung function. Future studies could investigate this using food frequency questionnaires or using dietary biomarkers [4042]. …”
Section: Discussionmentioning
confidence: 99%
“…These studies provide plausibility that differences between ethnic groups in maternal or childhood diets might be able to explain some of the differences in early adult lung function. Future studies could investigate this using food frequency questionnaires or using dietary biomarkers [4042]. …”
Section: Discussionmentioning
confidence: 99%
“…2) (74) . Since tissue and blood fatty acid profiles have been shown to be modified by dietary intake, they have been used as compliance markers for dietary supplementation studies (75)(76)(77) . However, it has yet not explicitly been demonstrated that phospholipid or total lipid content of cells can be used as a marker of dietary intake whilst the differences between different cell populations are confounding variables in the literature.…”
Section: Nutrition Research Reviewsmentioning
confidence: 99%
“…In this study, there was a good agreement between the dietary FFQ estimated fatty acid intake and the plasma fatty acid levels (84) . The Global Allergy and Asthma European Network of Excellence (GA 2 LEN) has shown that a reasonable association exists between estimates of dietary n-3 PUFA and total plasma phospholipid composition using the GA 2 LEN FFQ within the European countries that took part in the study (75) . In supplementation studies, while dietary estimates provide information about the dietary behaviour of individuals, the total cell or phospholipid content of fatty acids can be used as a reliable marker of incorporation.…”
Section: Nutrition Research Reviewsmentioning
confidence: 99%
“…Clinical assessment was also done and included measurement of height, weight, allergen skin prick test (SPT), blood samples for total and specific immunoglobulin E (IgE) and lung function. Detailed description of the study is provided elsewhere …”
Section: Methodsmentioning
confidence: 99%
“…The GA 2 LEN FFQ was validated in five EU countries, namely Finland, Portugal, Germany, Poland, and Greece) and demonstrated to be a good tool to assess midterm intake of foods, specifically essential polyunsaturated fatty acids (PUFAs). 21 The instrument has also been demonstrated to be an accurate tool to assess dietary sources of flavonoids. 26…”
Section: Respondents Sometimes Left Individual Items Blank On the Ffqsmentioning
confidence: 99%